Factors Influencing Recentralization of Local Government Functions in Uganda - Biryomumeisho, Stephen; Ocan, Johnson; Adyanga, Francis Akena (East African Nature and Science Organization, 2024)
The decentralisation system of governance is perceived as one of the recent public sector reforms to improve service delivery in Uganda. It is the transfer of authority from Central to Local Governments to execute their duties to improve service delivery. Various developing countries have praised Uganda’s decentralisation policy regarding the magnitude of the transfer of authority to the local level. However, since 2003, the Central Government started reversing the policy in terms of :  recentralization of the appointment of Chief Administrative Officers and Municipal Town Clerks and of recent City Town Clerks (for new cities in Uganda) from the District Service Commissions (DSCs) to the Public Service Commission,  recentralization of Kampala Capital City Authority (KCCA) under the management of the Executive Director, Procurement of drugs from the district health office to the National Medical Stores (NMS), recentralization of  the payroll and the recent recentralization of local revenue  collection from LGs.  This paper focuses on the factors influencing the recentralization of Local Government powers in Uganda. This is presumed to be evidence of the demise of decentralisation policy. From the reviewed articles, these factors include: accountability challenges, human resource management crisis, political interference by local authorities and lack of financial discipline among local authorities and fear of local autonomy. The paper concluded that recentralisation of Local Government functions reduced undue influence of local politicians though it accorded excessive powers to executive officers in Local Governments; human resource crisis was mainly caused by poor man power planning. Recentralisation of local revenue caused financial constraints at the local level and recentralisation of KCCA led to the weakening of the opposition but led to increases resources to develop the capital city. The paper recommended that the Parliament should harmonise with the central government on the issue of returning Local revenue collection and management at the local level; give reasonable powers to the local Governments to control top technical leadership; increase funding to Central Government staff to monitor Local Government programs and build the capacity of local leaders to improve service delivery